Cognitive training for older prisoners: a qualitative analysis of prisoners’ and staff members’ perceptions - Verhülsdonk, Sandra; Folkerts, Ann-Kristin; Hasenberg, Caroline; Bohn, Claire; Christl, Julia; Kalbe, Elke; Krieger, Theresia (Frontiers in Aging Neuroscience, 2024)
Introduction Correctional institutions are challenged by increasing numbers of older prisoners. Existing literature highlights the vulnerability of this group that is reflected by various somatic and mental health issues including cognitive dysfunctions. Although cognitive training studies in various target groups of older people have been conducted, there is lack of data regarding cognitive training in older prisoners. A structured cognitive group training program (“NEUROvitalis Prison”) with 12 weekly sessions was offered to male prisoners in Germany. Methods Post intervention an exploratory qualitative study was conducted. Prisoners (N = 18) and staff (N = 4) perspectives were explored by conducting face-to-face semi-structured interviews. Audiotaped data were fully transcribed and deductive-inductive content analyses applied. Results Both the prisoners and the staff perceived the cognitive training as very positive and stimulating. Moreover, the importance of the training was pronounced in terms of an increase in self-esteem and understanding of cognition and aging in the prisoners. Discussion Our data indicate that cognitive training may be a feasible and valuable intervention for older prisoners that will be appreciated by both inmates and staff. The qualitative data provide substantial insight into the experiences with the applied cognitive training program. Moreover, valuable modifications for future conduct can be derived.